Impact of Adjunct Femoral Patch Reconstruction on Graft Patency after Below the Knee Popliteal Bypass Implantation - Terézia B Andrási; Elke Dorner; Christof Kindler; Dieter Zenker; Christian F Vahl; Friedrich A. Schöndube (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
Introduction: Acknowledging the superior long term patency of infrainguinal saphenous bypass to distal popliteal artery, debate continues regarding the choice of alternative conduits and possible surgical adjuncts to improve inflow and graft salvage. The objective of this retrospective study was to determine the effectiveness of proximal anastomotic patch as adjunct to open surgical below the knee popliteal revascularization. Material and Methods: In a series of 132 distal popliteal bypass operations 63 non-reversed vein, 18 in situ vein and 51 Omniflow bypass conduits were used. Proximal anastomotic patch was applied in overall 28 patients: 19% in the non-reversed (12 patients), 50% in the in situ group (9 patients) and 13.7% in the Omniflow group (7 patients). Results: The reintervention rate was 7.9% in the non-reversed, 33.3% in the in situ and 31.4% in the Omniflow group. The most often complication was the proximal anastomotic stenosis (5.3%), followed by bleeding (3%), infection (1.5%) and distal anastomotic stenosis (1.5%). Patch reconstruction did not decrease incidence of reoperation (21.4% vs. 21.2% in the non-patch group), nor significantly influence bleeding, infection or thrombosis, however it reduced the overall rate of proximal anastomosis stenosis (0% vs. 6.7%, p=) and significantly improved patency rate at 3 years in the in situ group compared to the non-patch group (100% vs. 55.6%, p=0.02).